Screening of Potential Plant Growth Promoting Properties of Bacillus Species Isolated from Different Regions of Nepal - Pathak, Enish; Sanjyal, Arjun; Regmi, Chhatra Raj; Paudel, Saroj; Shrestha, Anima (Nepal Journal of Biotechnology, 2021)
The deleterious effects of intensive use of chemical fertilizers and pesticides in agriculture has led to the substantial research efforts on finding the alternatives to these agrochemicals. This study was aimed to isolate Bacillus species from soil of different regions of Nepal and screen for their ability to promote plant growth directly or indirectly by testing their ability to produce plant growth hormone indole acetic acid, hydrogen cyanide, ammonia and protease as well as phosphate solubilization. Thirty nine Bacillus strains were isolated from 25 soil samples of different regions of Kathmandu and Chitwan districts of Nepal. These isolates were tested for plant growth promoting traits in vitro. Among the total isolates, about 48.7% were indole acetic acid producers, 38.4% of the isolates showed the ability to solubilize the phosphate, 71.8% were able to produce ammonia and all the isolates had the ability to produce hydrogen cyanide and protease. The isolated strains showed positive results to maximum PGPR traits and exhibited a potential to be used as alternatives to chemical fertilizers and pesticides and could be used as low-cost bio-based technology to promote plant growth in the agricultural sector.